Cleft lip and palate: recommendations for dental anesthetic procedure based on anatomic evidences - Ivy Kiemle Trindade-Suedam; Bruno Felipe Gaia; Cheong Kuo Cheng; Paulo Alceu Kiemle Trindade; José Carlos da Cunha Bastos; Beatriz Silva Câmara Mattos (University of São Paulo, 2012)
Patients with cleft lip and palate usually present dental anomalies of number, shape, structure and position in the cleft area and the general dentist is frequently asked to restore or extract those teeth. Considering that several anatomic variations are expected in teeth adjacent to cleft areas and that knowledge of these variations by general dentists is required for optimal treatment, the objectives of this paper are: 1) to describe changes in the innervation pattern of anterior teeth and soft tissue caused by the presence of a cleft, 2) to describe a local anesthetic procedure in unilateral and bilateral clefts, and 3) to provide recommendations to improve anesthetic procedures in patients with cleft lip and palate. The cases of 2 patients are presented: one with complete unilateral cleft lip and palate, and the other with complete bilateral cleft lip and palate. The patients underwent local anesthesia in the cleft area in order to extract teeth with poor bone support. The modified anesthetic procedure, respecting the altered course of nerves in the cleft maxilla and soft tissue alterations at the cleft site, was accomplished successfully and the tooth extraction was performed with no pain to the patients. General dentists should be aware of the anatomic variations in nerve courses in the cleft area to offer high quality treatment to patients with cleft lip and palate.